A Stroke Mimic: A Case Report - Annia Martínez Rivas; Alexis Suárez Quesada; Yamila Espinosa Santisteban; Jirlén Moreno Torres; Alain Francisco Morejón Giraldoni (Revista Finlay, 2016)
Diseases mimicking a stroke are a major health problem for a large number of hospitals. This paper aims at presenting a disease that has a stroke-like presentation. The case of a 46-year-old man admitted to the stroke unit with a clinical and radiological diagnosis of cerebral infarction is presented. The patient developed fever and a serious deterioration of consciousness. Changes on computed tomography consistent with a brain abscess were observed. Broad-spectrum antibiotics were administered and a follow-up tomography was performed. Once the treatment was completed, the clinical and radiological suspicion of a brain abscess was confirmed.